2019
DOI: 10.2116/analsci.19r003
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm Shift in the Arena of Sample Preparation and Bioanalytical Approaches Involving Liquid Chromatography Mass Spectroscopic Technique

Abstract: Sample preparation is a highly important and integral part of bioanalysis for cleaning up the complex biological matrices and thereby minimizing matrix effect. Matrix effect can jeopardize the precise quantification and adversely affect the reliability of liquid chromatography-mass spectrometry-based analytical results by alteration of analyte ionization. Matrix components result in suppression or enhancement of the intensity of analyte response. In spite of the high specificity and selectivity of tandem mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 157 publications
0
7
0
Order By: Relevance
“…Several unique analytical approaches aimed at versatile ADC characterization were recently published including sensitive immunoassay, 32 sample preparation for intact-MS analysis 33 and intact RP-HPLC. 34 However, we are confident that this publication can serve as a useful guide to start pre-clinical process development of antibody conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…Several unique analytical approaches aimed at versatile ADC characterization were recently published including sensitive immunoassay, 32 sample preparation for intact-MS analysis 33 and intact RP-HPLC. 34 However, we are confident that this publication can serve as a useful guide to start pre-clinical process development of antibody conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other chromatographic technique, RPLC has much higher separation power and a great variety of columns. Therefore, it was reported that over 80% separation work was achieved by RPLC [25‐28]. In 2D‐LC system, RP/RPLC was utilized to get high column efficiency and compatibility with MS. To add orthogonality of 2D‐LC, different mobile and stationary phases were selected in 2D separation.…”
Section: Resultsmentioning
confidence: 99%
“…A forced degradation study is carried out at severe conditions when compared with accelerated conditions to evaluate the molecule stability. 4,5 As per the ICH (International Council for Harmonization) guidelines, to file a dossier registration, it is mandatory to perform stress studies of the drug. 6,7 These degradation studies will help find the suitable conditions for the storage.…”
Section: Introductionmentioning
confidence: 99%